ANALISIS KINERJA ORGANISASI PUBLIK PADA PDAM KOTA MOJOKERTO - Suwaji, Rifki (Dinamika Governance : Jurnal Ilmu Administrasi Negara, 2020)
The current regional autonomy is a new thing for every region in Indonesia, because the autonomy proclaimed through Law Number 32 Year 2004 gives more freedom for the region to express itself towards the direction of development through empowering the local community itself. the complexity of the problems that exist in District of Lanny Jaya, such as in efforts to improve community welfare and coupled with physical development that must be carried out by the District of Lanny Jaya Government, in order to improve services to the community. The purpose of this study is the influence of the strategic environment, organizational culture and strategic planning on the performance of public organizations in the Office of Community Empowerment and Village District of Lanny Jaya Papua of Province Government. The sample of this study was 100 residents District of Lanny Jaya. The research data in the form of primary data obtained through questionnaires, while secondary data obtained from the community on District of Lanny Jaya. The analytical tool used is Partial Least Square (PLS). The results of this study indicate that, (1) strategic environment has a significant positive effect on strategic planning (2) organizational culture has a significant positive effect on strategic planning (3) strategic environment has a non-significant effect on organizational performance (4) organizational culture has a significant positive effect on performance organization (5) strategic planning has a significant positive effect on organizational performance. DOI : https://doi.org/10.33005/jdg.v10i2.2280